2018
DOI: 10.1177/2055116918804305
|View full text |Cite
|
Sign up to set email alerts
|

Congenital peritoneopericardial diaphragmatic hernia in a family of Persian cats

Abstract: Case series summaryThe congenital midline defects of peritoneopericardial diaphragmatic hernia (PPDH) and omphalocele are believed to be related developmental defects, and have both been described in cats and dogs. This case series describes multiple cases of PPDH and omphalocele in related cats. The majority of cats affected with midline defects (PPDH or omphalocele) were male, consistent with previous reports of male overrepresentation.Relevance and novel informationThis is the first report of a family of Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
0
13
1
3
Order By: Relevance
“…Previous reports suggested that the detection of the PPDH often happened by chance from the routine examination (Margolis et al, 2018). However, the animals showed clinical signs in this present case report, such as labored breathing and intermittent cough, and surgical treatment is the best effective treatment.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Previous reports suggested that the detection of the PPDH often happened by chance from the routine examination (Margolis et al, 2018). However, the animals showed clinical signs in this present case report, such as labored breathing and intermittent cough, and surgical treatment is the best effective treatment.…”
Section: Discussioncontrasting
confidence: 49%
“…Peritoneopericardial diaphragmatic hernia (PPDH) is a common congenital pericardial defect encountered in cats (Khan et al, 2019;Hodgkiss-Geere et al, 2015;Banz and Gottfried., 2010;Margolis et al, 2018). PPDH is an abnormal development of the dorsolateral septum transversum or the lateral pleuro-peritoneal folds that cause the communication between the peritoneal and pericardial sac through the diaphragm (Berry et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The few reported cases in animals were diagnosed in dogs and cats, calves, horses and alpacas. [1][2][3][4][5][6][7][8][9] This condition has not been reported to date in any wild counterparts, especially not in wild antelope species, as documented in this case.…”
Section: Introductionmentioning
confidence: 81%
“…Maine coon cats, Himalayan cats and Weimaraner dogs showed an abnormal high prevalence for this abnormality, indicating the possibility of a heritable predisposition for this condition in these breeds 3 . Congenital peritoneopericardial diaphragmatic hernias in cats and dogs are often reported in conjunction with a variety of co‐existing congenital defects, that is, skeletal and cardiac abnormalities 3,7 . Reports on species, other than companion animals, with congenital peritoneopericardial diaphragmatic hernias are limited to calves, alpacas and horses 4–6,14 .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] One study suggested a probable hereditary basis for PPDH in Persian cats. 13 Diagnosis of PPDH can usually be achieved with plain radiography. The most common abnormal findings on thoracic radiography include the detection of an enlarged and globoid cardiac silhouette, presence of abdominal organs in the pericardial sac, poorly appreciable diaphragmatic borders and possible identification of a mesothelial remnant between the caudal cardiac silhouette and the diaphragm (usually seen ventral to or superimposed over the caudal vena cava on lateral views).…”
Section: Discussionmentioning
confidence: 99%